Exploring the Impact of Video-Based Listening Activities on Speaking Proficiency of English For Foreign Language Learners - Maulana, Hafiz (Published by Institut Teknologi Pendidikan Indonesia, 2024)
This study investigates the impact of video-based listening activities on the speaking proficiency of English as Foreign Language (EFL) learners at the junior high school level in Indonesia. The research employed a pre-experimental design with a one-group pretest-posttest approach, involving 18 eighth-grade students from SMP Muhammadiyah Parakan, South Tangerang. The study aimed to address the challenges faced by EFL learners in developing speaking skills and explore the potential of multimedia learning in enhancing language acquisition. Data were collected through pre-test and post-test speaking assessments, evaluating voice quality, pronunciation, speech duration, and overall performance. The intervention consisted of structured video-based listening activities designed to improve both receptive and productive language skills. Statistical analysis, including paired t-tests and effect size calculations, was conducted to determine the significance and magnitude of the intervention's impact. Results revealed a significant improvement in students' speaking proficiency following the intervention. The mean score increased from 65.55 in the pre-test to 77.77 in the post-test, with a notable shift in score distribution towards higher performance categories. The paired t-test confirmed the statistical significance of this improvement (p = 0.001 < 0.05). These findings support the effectiveness of video-based listening activities in enhancing EFL learners' speaking skills, aligning with cognitive multimedia learning theory. The study contributes to the growing body of evidence supporting the integration of multimedia resources in language education. Recommendations include systematic integration of video-based activities into EFL curricula, teacher training in effective video content selection and use, and further research with larger sample sizes and extended intervention periods.